GENE FORRESTER’S SEXUAL IDENTITY DEVELOPMENT IN JOHN KNOWLES’S A SEPARATE PEACE (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2018)
Abstract This study is aims finding the influences of Gene Forrester to be a homosexual guy as a main character in John Knowles A Separate Peace. A gay who is being heterosexual at the frist time, but finally a homosexuality is his sexual identity. There are many influences that can help to develop the sexual identity. This literary study applies the concept of homosexuality, the concept of gender role, and homosexual development process. Those theories are used to analyze Gene Forrester on his sexual identity. The main data of this study is taken from John Knowles novel in the form of conversations, questions, direct and indirect speeches that represent the problems of the study. Based on the analysis, this study reveals that the process of Gene Forrester’s sexual identity development that starts from his scare about himself and can not be confidence on the public that he is a gay untill he becomes confidence and acknowledge about his sexual identity with other gay. Keywords: gay, homosexuality, sexual identity, the concept of gender, the concept of homosexuality Abstrak Tujuan ditulisnya skripsi ini adalah untuk menemukan pengaruh – pengaruh dari Gene Forrester menjadi pria homoseksual sebagai karakter utama di dalam novel John Knowles yang berjudul A Separate Peace. Seorang gay yang awalnya adalah sebagai pria normal, akan tetapi homoseksual lah yang menjadi identitas seksualnya pada akhirnya. Ada banyak pengaruh – pengaruh yang dapat membantu untuk mengembangkan identitas seksual. Tujuan pembahasan ini adalah untuk mengungkapkan konsep dari homoseksualitas, konsep dari peran jender, dan proses berkembangnya homoseksual. Teori – teori tersebut digunakan untuk menganalisis identitas seksual dari Gene Forrester. Data – data dari pembahasan tersebut diambil dari novel John Knowles dalam bentuk percakapan – percakapan, pertanyaan – pertanyaan, dan obrolan langsung ataupun tidak langsung yang menunjukkan masalah – masalah di dalam pembahasan. Berdasarkan analisis, pembahasan tersebut mengungkapkan bahwa proses perkembangan identitas seksual dari Gene Forrester berawal dari ketakutannya terhadap dirinya sendiri dan tidak dapat nyaman di publik bahwa dirinya adalah seorang homoseksual sampai akhirnya dia menjadi nyaman dan dapat mengakui identitas seksualnya dengan pria homoseksual lainnya. Kata Kunci: gay, homoseksualitas, identitas seksual, konsep jender, konsep homoseksualitas